Development and Initial Validation of a Scale to Measure Cognitive Demands of Flexible Work - Prem, Roman; Kubicek, Bettina; Uhlig, Lars; Baumgartner, Vera; Korunka, Christian (Frontiers in Psychology, 2021)
With globalization, digitalization, and the spread of information and communication technologies, rules regulating work have been softened or completely abolished. Consequently, employees face additional cognitive demands to plan, structure, and coordinate their work. To capture these demands of contemporary work, we constructed and initially validated the Cognitive Demands of Flexible Work (CODE) scale. The scale comprises four subscales (i.e., structuring of work tasks, planning of working times, planning of working places, and coordinating with others). We initially validated the scale in three independent studies (overall N = 1129) in German and English. Confirmatory factor analyses supported the four-factor structure, as well as scalar invariance, of the different language versions. Moreover, the subscales showed convergent and divergent validity with related constructs such as requirements for problem solving or autonomy. The criterion validity for emotional exhaustion, engagement, positive work rumination, negative work rumination, and problem-solving pondering suggested that cognitive demands of flexible work can be construed as challenge demands. However, relationships with emotional exhaustion were not significant. Overall, the CODE scale was shown to be a reliable and valid instrument to measure cognitive demands of flexible work.